Detective/text/critic - Sorfa, David (Department of English Language and Literature, 2016)
This thesis grapples with the curious relationship of the metaphors of detection and reading. Detective fiction is often seen as an enactment of reading, while the literary critic is often described in terms of detection, investigation and interrogation. The Introductory section discusses the implications that such a self-reflexive and reflecting involvement has for narrative, the self, logic and the very institution of academic literary criticism itself. The notion of a detective genre, and genre-criticism in general, is put into question by analysing the legal and coercive nature of a literary concept that styles itself as objective, scientific and historical. The power of the critic to construct genre is likened to the legal capacity of the detective and a polemical call is made to re-examine the academy's resulting claims of authority. An analysis of the crime of incest in two films, Roman Polanski's Chinatown and Jack Nicholeson's The Two Jakes, is used to further problematise the notion of the law. Claude Levi-Strauss' work on kinship structures helps to point to the aporetic and contradictory position that incest can be seen to occupy in the formation of human society. Criminal anthropology provides an interesting frame for this discussion. Thomas Pynchon's The Crying of Lot 49 is used to explore the fundamental uncertainty in which the detective/reader necessarily finds herself. Sigmund Freud's concept of the uncanny is introduced to account for the interpreter's state of unease in the face of ambiguity. Finally, a literary essay, Jacques Derrida's "Structure, Sign and Play in the Discourse of the Human Sciences", is read rather as a form of detective story than as a factual analysis, whether this experiment is successful will be up to the reader. The overriding claim of this thesis is that there is no such thing as perception.